Proceedings of the 4th International Conference on Sustainable Innovation 2020–Technology, Engineering and Agriculture (ICoSITE 2021
DOI: 10.2991/aer.k.210204.048
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Detritivores, Pollinators, and Neutral Insects on Surjan and Conventional Rice Field Ecosystems

Abstract: Surjan and conventional rice fields are two rice farming systems grown in polyculture and monoculture. Differences in agricultural systems can affect insect diversity. This study aimed to determine the effect of the Surjan and conventional rice field ecosystems on the diversity and abundance of detritivores, pollinators, and neutral insects. The research was conducted in Panjatan District, Kulon Progo, Yogyakarta with a survey method in three areas of Surjan and conventional rice fields. Insect samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…However, the abundance of pests in both farming systems was relatively the same (Paired t-test, P=0.937) (Figure 4b). This result contrasts with our previous study in which there was no difference in the species richness of detritivores, pollinators, and neutral insect species in the Surjan paddy field, but their abundance was higher in that field (Herdiawan et al 2021).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the abundance of pests in both farming systems was relatively the same (Paired t-test, P=0.937) (Figure 4b). This result contrasts with our previous study in which there was no difference in the species richness of detritivores, pollinators, and neutral insect species in the Surjan paddy field, but their abundance was higher in that field (Herdiawan et al 2021).…”
Section: Resultscontrasting
confidence: 99%
“…In our previous study, the different configurations of Surjan and Lembaran paddy fields affect the biodiversity of detritivores, pollinators, and neutral insects (Herdiawan et al 2021). This generates an interesting question about the diversity of pests in both farming systems and whether the configuration affects the abundance.…”
Section: Introductionmentioning
confidence: 98%
“…Nowadays, the use of bioindicators has been progressively significant through determining the association between biotic factors and the abiotic, particularly the pesticide application to the rice field. The differences in pesticide application are assumed to affect the population dynamic of neutral insects [38]. The neutral insect population in Inpari 32 HDB was significantly less than in Inpari 42 GSR at 40 days of plant age or day zero (the day of first insecticides application).…”
Section: Resultsmentioning
confidence: 99%
“…According to the findings of our previous research, surjan paddy fields impact the diversity of detritivores, pollinators, neutral insects, and pest insects (Herdiawan et al, 2021;Trisnawati et al, 2022b). As a result, it is essential to study the diversity of predators found in surjan's paddy fields to establish credible insights regarding the ecosystem's condition and the relationships between its components.…”
Section: Introductionmentioning
confidence: 89%